Analysis of the Impact of Inflation, Unemployment, Debt-to-GDP ratio, and GDP Growth on the Probability of Default in the Countries of the Three Seas Initiative - Dančáková, Klára; Čihák, Jakub; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the relationship between the probability of default (PD) and macroeconomic variables in the Three Seas Initiative (3SI) countries and compares how the dynamics between these indicators changed after 2019. It also analyses cross-country differences within the initiative and shows that the factors most strongly influencing default probabilities vary substantially across member states. The findings confirm that the mechanisms governing credit-risk dynamics prior to 2020 changed markedly following the COVID-19 pandemic, indicating the presence of a structural break. These results imply that supporting financial stability in the region requires considering the individual structural characteristics of each economy and their differing sensitivities to external shocks. The panel data covering the period 09/2014–03/2025 were analysed using a PVARFEOLS model. In the final part of the thesis, country-specific models were identified based on the AkaikeInformation Criterion (AIC), capturing the variables that most significantly explain the variability in the probability of default.
Vedoucí práce: Jakub Čihák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses